Shatter me - Mafi, Tahereh (United Kindgdom Allen and Unwin Publishing, 2013)
Juliette must make a choice. Be a weapon. Or a warrior. Combining a crumbling dystopian world with a compelling heroine who has inexplicable powers, Shatter Me is a mesmerising thriller. 'Addictive, intense, and oozing with romance.' - Lauren Kate, author of Fallen